Meteor‐Ablated Aluminum in the Mesosphere‐Lower Thermosphere. Issue 2 (19th February 2021) - Plane, John M. C.; Daly, Shane M.; Feng, Wuhu; Gerding, Michael; Gómez Martín, Juan Carlos
Abstract: The first global atmospheric model (WACCM‐Al) of meteor‐ablated aluminum was constructed from three components: The Whole Atmospheric Community Climate Model (WACCM6); a meteoric input function for Al derived by coupling an astronomical model of dust sources in the solar system with a chemical meteoric ablation model; and a comprehensive set of neutral, ion‐molecule and photochemical reactions relevant to the chemistry of Al in the upper atmosphere. The reaction kinetics of two important reactions that control the rate at which Al + ions are neutralized were first studied using a fast flow tube with pulsed laser ablation of an Al target, yielding k (AlO + + CO) = (3.7 ± 1.1) × 10 −10 and k (AlO + + O) = (1.7 ± 0.7) × 10 −10 cm 3 molecule −1 s −1 at 294 K. The first attempt to observe AlO by lidar was made by probing the bandhead of the B 2 Σ + (v′ = 0) ← X 2 Σ + (v″ = 0) transition at λair = 484.23 nm. An upper limit for AlO of 60 cm −3 was determined, which is consistent with a night‐time concentration of ∼5 cm −3 estimated from the decay of AlO following rocket‐borne grenade releases. WACCM‐Al predicts the following: AlO, AlOH and Al + are the three major species above 80 km; the AlO layer at mid‐latitudes peaks at 89 km with a half‐width of ∼5 km, and a peak density which increases from a night‐time minimum of ∼10 cm −3 to a daytime maximum of ∼60 cm −3 ; and that the best opportunity for observing AlO is at high latitudes during equinoctial twilight. Key Points: Experimental study of the reactions of AlO + with O and CO provides closure for the neutral and ion‐molecule chemistry of meteor‐ablated Al Atmospheric model of Al is constructed by adding this chemistry and an Al meteoric source function to the WACCM chemistry‐climate model The model predicts a nighttime AlO density of ∼10 cm −3, consistent with an AlO upper limit of 60 cm −3 determined from a lidar campaign Plain Language Summary: Around 30 tons of cosmic dust particles enter the Earth's atmosphere each day. Aluminum (Al) makes up around 1.4% of these particles by mass. This study explores what happens to the Al which ablates from cosmic dust in the region between 80 and 110 km. In the first part of the second, laboratory experiments are described to measure two reactions of aluminum oxide ions which control how quickly ionized aluminum species are neutralized. A chemical network of 36 reactions of Al species is then put into a chemistry‐climate model, along with the predicted injection rate of Al from dust ablation. The model simulates well the concentration of Al ions measured by rocket‐borne mass spectrometry. We then describe an attempt to measure the concentration of AlO, using laser sounding of an unusually strong optical transition of AlO. This yielded a very small upper limit to the AlO concentration, shown to be consistent with the atmospheric model and the rate at which AlO disappears following release from rocket payloads above 90 km.